Understanding Maternal Support for Autonomy in Young Children with Down Syndrome. Issue 2 (June 2016) - Gilmore, Linda; Ryan, Belinda; Cuskelly, Monica; Gavidia‐Payne, Susana
Abstract: Prior research has highlighted the importance of supporting the autonomy of children with Down syndrome from early childhood. There is some evidence to suggest that mothers of children with Down syndrome are more directive than those whose children are developing typically. However, the factors that contribute to maternal autonomy supportive vs. directive behaviors are not well understood. The current study aimed to explore the value and importance that mothers place upon their child's autonomy, as well as the specific factors that influence the support they provide. Interviews were conducted with 14 mothers of young children with Down syndrome. It was revealed that mothers held aspirations for their children's future that included autonomy and independence; however, their capacity to promote autonomy was sometimes constrained by a range of child and family factors, as well as by their focus on developing skills for independent functioning. Understanding the factors that may constrain support for autonomy represents an essential step in the process of designing interventions for promoting maternal support for autonomy in families of children with Down syndrome and other developmental disabilities.